Analisis Strategi Personal Branding Fadil Jaidi Sebagai Influencer di Media Sosial Instagram - Fasya Iffat Rosi; Iky Putri Aristhya (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study explores Fadil Jaidi's personal branding strategy as an influencer on Instagram by examining the values that shape his image in the eyes of his audience. Using a qualitative descriptive approach based on content analysis, this study employs Peter Montoya's framework of The 8 Laws of Personal Branding, namely specialization, leadership, personality, distinctiveness, visibility, unity, persistence, and goodwill, to assess the consistency and effectiveness of his branding efforts. The analysis shows that Fadil's strength lies in his distinctiveness and personality, which are conveyed through his unique humor and authentic representation of everyday life, reinforced by his visibility through consistent posts. In addition, aspects of goodwill and unity are evident in his positive interactions and the harmony between the values he promotes and the content he shares. These findings confirm that the success of Fadil's personal branding is not only based on his humorous character, but also on his authenticity, consistency, and closeness to his audience. This study has limit because it only looks at Fadil's content on few  social media platforms within a limited time frame, and the assessment is based on the researcher's point of view, so the results do not fully describe Fadil's personal branding as a whole. This study shows that Fadil Jaidi's personal branding on Instagram has been successfully built through authentic humor, consistent content, and closeness to his audience. However, because this study only looked at content on a specific platform and time period and was influenced by the researcher's perspective, further research is needed to obtain more comprehensive results.